Designing of Decision Support System for Determining the Underlying Cause of Death in Mortality Codification - Riska Pradita; Desfa Anisa; Anggia Natasha Dwiansyah (Indonesian Journal Publisher, 2026)
Inaccuracies are often encountered in determining the Underlying Cause of Death (UCoD), which can impact the quality of reported mortality data. In this case, a system is needed to assist coders in determining the UCoD. Clinical Decision Support System (CDSS) is a system designed to assist decision-making in patient clinical management, including in determining UCOD. The purpose of this study was to design a CDSS in determining UCOD mortality codification. The research method used is descriptive research with an Action Research design consisting of four stages: Diagnosing, Planning, Taking, and Evaluating Action. The objects of this study were SIMRS, medical record documents, and death certificates. Data were collected through interviews and documentation studies. The research results obtained were user requirements consisting of features, databases, and system displays. The design was carried out using UML modeling such as Flowcharts, Use Case Diagrams, Activity Diagrams, Class Diagrams, Data Flow Diagrams, and Prototypes. The evaluation results showed that the designed CDSS was acceptable to users as a tool in determining UCOD, with a value above the global average score (77). The conclusion of this study obtained that the CDSS design is considered effective in helping coders to determine UCoD.